Revisiting the Role of Intravitreal Triamcinolone in Diabetic Macular Edema: 12-Month Outcomes after Bevacizumab Failure - Sukhum Silpa-archa; Variya Nganthavee; Peranut Chotcomwongse; Pawas Lalitwongsa; Paisan Ruamviboonsuk (Ophthalmology and Therapy)
Abstract Introduction Refractory diabetic macular edema (DME) is challenging in resource-limited settings, where costly alternatives such as non-bevacizumab anti-vascular endothelial growth factors (VEGFs) and corticosteroid implants are inaccessible. In Thailand, budget constraints exclude these drugs from healthcare schemes covering 92% of the population, a common issue in developing Asian countries. Therefore, this study aimed to evaluate the treatment outcome of repeated intravitreal triamcinolone acetonide (IVTA) dosages for DME refractory to intravitreal bevacizumab over a 12-month period using a decision algorithm. Methods This was a comparative retrospective study. The included patients were randomly divided into two groups that received either 2 mg or 4 mg IVTA, following a decision algorithm. The primary outcome was the difference in central macular thickness (CMT) between the 2 mg IVTA and 4 mg IVTA groups at 6-month and 12-month follow-up visits. Results Overall, 81 eyes (62 patients) with DME refractory to bevacizumab were enrolled. The study involved 53 eyes (37 cases) divided into two groups: group 1 (2 mg IVTA) of 14 eyes, and group 2 (4 mg IVTA) of 39 eyes. The 4 mg IVTA group had a higher initial CMT than their 2 mg IVTA counterparts (P = 0.02). This difference disappeared after 6 and 12 months. The improvement in CMT in both groups was maintained across the 6- and 12-month follow-up periods compared with baseline. Univariate logistic regression analysis revealed that patients with thinner CMT before IVTA treatment had a greater probability of being DME-free over long-term follow-up. Conclusions Repeated IVTA treatments for DME refractory to bevacizumab over a 12-month period demonstrated efficacy and appeared to have a comparable safety profile. Patients with thinner CMT before IVTA treatment had a greater probability of remaining DME-free after IVTA treatment.